Pemaknaan Spiritual Berdampak Terhadap Psychological Distress dan Kontrol Mean Arterial Pressure Pada Pasien Hipertensi - Faisal Amir; Lantin Sulistyorini; M. Suhron; Sitti Sulaihah (Health and Technology Journal (HTechJ), 2023)
Hypertension is a disease that can cause various complications and is made worse by psychological distress, where cases are increasing at the Bangkalan Community Health Center. This research aims to analyze the correlation between spiritual meaning in regulating psychological distress and mean arterial pressure (MAP) in hypertension patients. This research method is correlation analytic with a cross-sectional approach with the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guideline. population of 76 patients and a sample of 62 taken using simple random sampling. The independent variable is spiritual meaning, measured using the Daily Spiritual Experience Scale (DSES). Meanwhile, the dependent variable is distress, measured by the Kessler Psychological Distress Scale and the mean arterial pressure (MAP) value. The collected data was then subjected to statistical tests using Spearman ranks with an alpha value of 0.05. The research results show a relationship between spiritual meaning and psychological distress with a p-value of 0.016 < 0.05 and a correlation coefficient of -0.305. Spirituality is also significantly related to the mean arterial pressure (MAP) value with p value 0.005 < 0.05, and the correlation coefficient is -0.351. Spirituality has an impact on reducing psychological distress, affecting the function of the Hypothalamus Pituitary Adrenal (HPA) Axis and Sympathetic Adrenal Medullary (SAM) Axis. The SAM Axis will balance the secretion of norepinephrine (NE) and epinephrine (E), which affects the balance of contraction of smooth cardiac muscle cells, vasoconstriction and vasodilation, heart rate, and normalizes sodium levels so that it can control blood pressure in hypertensive patients.